1998
DOI: 10.1063/1.121513
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of photoinduced expansion in hydrogenated amorphous silicon using bending detected optical lever method

Abstract: Photoinduced structural change in hydrogenated amorphous silicon (a-Si:H) has been studied by a sensitive bending detection method using an optical lever. We observed that a-Si:H films show not only thermal expansion due to a photothermal effect but also residual and persistent expansion after light soaking. The volume change is recovered by thermal annealing at 200 °C. A dehydrogenated sample annealed at 550 °C and a microcrystalline sample, in which photoinduced defects are not created, show little photoindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 8 publications
3
31
0
Order By: Relevance
“…As a matter of fact, there has been a great deal of research on lightinduced volume changes [50]. Various beam bending experiments have been performed using samples consisting of long and narrow pieces of thin glass or quartz substrates coated with a-Si:H [51][52][53][54][55][56][57]. These results reveal that lightinduced volume expansion follows a stretched exponential behavior, usually showing saturation at dV /V ∼ 10 −3 [29].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, there has been a great deal of research on lightinduced volume changes [50]. Various beam bending experiments have been performed using samples consisting of long and narrow pieces of thin glass or quartz substrates coated with a-Si:H [51][52][53][54][55][56][57]. These results reveal that lightinduced volume expansion follows a stretched exponential behavior, usually showing saturation at dV /V ∼ 10 −3 [29].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that there exists some correlation between the photoinduced dilation and the photodegradation in undoped a-Si:H films [3][4][5]. A simple scenario to understand this correlation is that the creation of dangling bonds DN d itself brings the dilation DV =V of amorphous Si network.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, photoinduced volume changes (photoinduced structural changes) in a-Si:H films have been investigated by some groups [3][4][5][6][7]. We have previously reported that there exists some correlation between the photoinduced dilation and the photodegradation in undoped a-Si:H films [3][4][5].…”
Section: Introductionmentioning
confidence: 96%
“…It is reported that light soaking or high-energy-particle irradiation made the amorphous network of a-Si:H films to be reorganized, leading to a change in the structural order of the films [5][6][7][8][9] . The local distortions of amorphous network due to higher density defects in the irradiated a-Si:H films result in a change of structural order [9] and a macroscopic volume expansion [10] . Chini et al [11] have reported the formation of 50-260 nm a-Si:H layers on the high-energy-particle-irradiated crystalline silicon surfaces by means of transmission electron microscopy, despite the fact that the penetration depth of high energy particles in crystalline silicon was far beyond the formed amorphous-layer thickness.…”
Section: Introductionmentioning
confidence: 99%